2012
DOI: 10.1002/rcm.6117
|View full text |Cite
|
Sign up to set email alerts
|

Reaction pathways of Rh+ (3F and 1D) with CH3OCH3 in the gas phase

Abstract: Based on the results, it is believed that the demethanation reaction of dimethyl ether mediated by transition metal monocation would preferably occur through the C-O bond activation pathway. Combined with previous studies, a general reaction mechanism of the transition metal monocation with dimethyl ether is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The specific rate constants could all be represented in the form of eq A3 of the Appendix with the parameter s* ≈ 5. 5. The relevant well depths, also required for the calculation of k(E), were taken as that for 6 1 (mechanism a and c) and for 4 1 (mechanism b).…”
Section: ■ Kinetic Modeling Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specific rate constants could all be represented in the form of eq A3 of the Appendix with the parameter s* ≈ 5. 5. The relevant well depths, also required for the calculation of k(E), were taken as that for 6 1 (mechanism a and c) and for 4 1 (mechanism b).…”
Section: ■ Kinetic Modeling Resultsmentioning
confidence: 99%
“…The gas phase reactions of transition metal cations with dimethyl ether, CH 3 OCH 3 , have frequently been used as a prototype for the activation of CO bonds in organic molecules (see, e.g., refs ). Depending upon the reaction conditions, one has the possibility of adduct formation or demethanation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous computational and experimental studies that addressed reactions encompassing ethers and TM atoms or ions showed that the reaction of C–O bond cleavage begins with the TM binding to the oxygen atom of the ether, forming an adduct. Following an intermediate structural arrangement, the reaction terminates with hydrogen migration. Figure shows a possible reaction pathway for methoxyethane activation, which is similar to the mechanism outlined in the ether and TM ions studies . The metal atom first binds to the oxygen atom of methoxyethane to form the adduct [MO­(CH 3 CH 2 )­(CH 3 )].…”
Section: Introductionmentioning
confidence: 75%
“…The Minnesota functionals (M06 and M06L) were considered due to the inclusion of spin kinetic energy, and their parametrization includes a number of TM species. B3LYP was selected due to its wide use and its utility in the prediction of TM compound geometries, 27 whereas PBE0, the other hybrid-GGA functional, was chosen because it performed well in a study on the C−O bond cleavage of dimethyl ether by TM ions. 29 The final functional, B2PLYP, is a double-hybrid-GGA functional and includes the nonlocal correlation energy predicted at the level of second-order many body perturbation theory.…”
Section: ■ Introductionmentioning
confidence: 99%